Arte e educação: a importância do professor de arte no ensino - Santos, Aldenize Leal dos (Brasil, 2024)
The present work is based on concerns about Art Teaching and the Art teacher, these concerns were originated in high school and reinforced in supervised internships, the absence of these professionals in schools is constant and vaguely has their presence considered relevant to the formation of students. Bringing this discussion is essential to change the irrelevant view that predominates in society about the importance that the art teacher has in education. In this sense, the problem that this research aims to address is: How does the absence of the Art teacher impact the students' education? The objective of this work is to provide a reflection on the relevance that the Art teacher/educator plays in the education of students. In addition to knowing the history of Art Teaching in Brazil, teacher training and analyzing the difficulties and weaknesses in Art Teaching in a state school that has only Elementary I, located in the city of Parintins, in Amazonas. The bibliographic research is based on the studies of Ana Mae Barbosa, Maria Heloisa Ferraz, Maria Resende e Fusari, João Francisco Duarte Jr and Rejane Galvão Coutinho. For a better understanding of how the teaching of Art is being developed in a public school in Parintins, the principles of school ethnography were used, using the technique of participant observation, informal conversations and records in the field diary. Art in this school is conducted by teachers with training in teaching and pedagogy, who face difficulties mainly in the lack of knowledge about the contents of this discipline, compromising the training of students, who in turn do not acquire knowledge about the different cultural manifestations and local culture, in addition to the traditional methods used by the teachers preventing them from creating, imagine and not be interested in participating in the activities. In order for students to enjoy a comprehensive education in Art, it is necessary to have laws that guarantee the performance of teachers with specific training. And thinking about the current scenario, it is important that continuing education courses in Art Education are offered to pedagogues and other teachers without specific training who work in this discipline.